2021
DOI: 10.1164/rccm.202007-2924le
|View full text |Cite
|
Sign up to set email alerts
|

Is IL-6 the Right Target in COVID-19 Severe Pneumonia?

Abstract: Funding : This work was supported by grants (MB) from the AOI (Appel d'Offre Interne)-COVID-2020 and Crowfunding (https://thellie.org/covid-19). Ethics approval and consent to participate : Oral consent was obtained from the patient or their legal representatives. Approval was obtained from the ethics committee (Comité de Protection des Personnes Sud-MEDITERRANEE V) (2017-A03404-49) and an amendment was obtained to include supplementary patients with COVID-19. Conflicts of interest: We declare no conflict of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…At baseline respiratory severity, COVID-19 patients had a significantly longer duration of MV (15 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] vs. 4 [0-14.5]; p = 0.0049), and ICU stay (p = 0.0274) and higher rate of ventilator-acquired pneumonia (p = 0.001) than non-COVID-19 patients ( Table 1). The 30-day mortality rate was 6% (n = 2) in the non-COVID-19 group and 4% (n = 1) in the COVID-19 group (p = 1.00).…”
Section: Covid-19 Patients Had a Significantly Longer Duration Of Mecmentioning
confidence: 99%
See 2 more Smart Citations
“…At baseline respiratory severity, COVID-19 patients had a significantly longer duration of MV (15 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] vs. 4 [0-14.5]; p = 0.0049), and ICU stay (p = 0.0274) and higher rate of ventilator-acquired pneumonia (p = 0.001) than non-COVID-19 patients ( Table 1). The 30-day mortality rate was 6% (n = 2) in the non-COVID-19 group and 4% (n = 1) in the COVID-19 group (p = 1.00).…”
Section: Covid-19 Patients Had a Significantly Longer Duration Of Mecmentioning
confidence: 99%
“…11 Department of Internal Medicine and Clinical Immunology, Dijon Bourgogne University Hospital, Dijon, France. 12 Department of Internal Medicine and Systemic Diseases, Dijon Bourgogne University Hospital, Dijon, France. 13 Geriatrics Internal Medicine Department, Dijon Bourgogne University Hospital, Dijon, France.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, from our findings, it seems that the inhibition of IL-6 alone may not be adequate to mitigate the risk of mortality in patients with COVID-19, at least in certain subpopulation of patients with more severe disease [11]. Indeed, a recent prospective study by Blot et al [12], which compared the plasma concentrations of IL-6 among patients with COVID-19 associated pneumonia and patients with pneumonia other than COVID-19, reported that the plasma concentrations of IL-6 were significantly lower among the patients with COVID-19 associated pneumonia relative to the patients with pneumonia other than COVID-19 (121.0 pg/mL versus 460.4 pg/mL).…”
Section: Discussionmentioning
confidence: 72%
“…Leptin is secreted by adipose tissue and acts as a central pro-inflammatory regulator of innate and adaptative immune responses, especially by increasing T-cell proliferation and Th-1 response [ 5 ]. Interestingly, we recently reported that both alveolar and plasma concentrations of CXCL10, a Th-1 chemokine, were higher in COVID-19 patients than in non-COVID-19 patients, and were independently associated with a longer duration of MV [ 8 , 12 ]. Accordingly, we tried to unravel the link between adipokines and inflammatory cytokine production in patients with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%